2020
DOI: 10.1038/s41598-020-75225-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequential laxative-probiotic usage for treatment of irritable bowel syndrome: a novel method inspired by mathematical modelling of the microbiome

Abstract: The gut microbiome plays an important role in human health. However, its response to external intervention is complex. A previous study showed that the response to Clostridium butyricum (CB) treatment of irritable bowel syndrome (IBS) is heterogeneous. We proposed that mathematical model simulation of the microbiota may help to optimize the management of IBS-associated microbiota. In this study, a novel mathematical non-extinction and defecation normalized (NEDN) model was generated for stable simulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The transplanted probiotics met indigenous microbiome-mediated mucosal colonization resistance in mice and even a specific colonization resistance in a person-, strain-, and region- dependent manner in humans[ 113 ]. Our recent mathematical model studies also suggested intriguing behavior of microbiome in response to probiotic supplement[ 114 ]. For FMT, the risk of unknown infections is still inevitable even after rigorous tests on the donors.…”
Section: Discussionmentioning
confidence: 99%
“…The transplanted probiotics met indigenous microbiome-mediated mucosal colonization resistance in mice and even a specific colonization resistance in a person-, strain-, and region- dependent manner in humans[ 113 ]. Our recent mathematical model studies also suggested intriguing behavior of microbiome in response to probiotic supplement[ 114 ]. For FMT, the risk of unknown infections is still inevitable even after rigorous tests on the donors.…”
Section: Discussionmentioning
confidence: 99%
“…The pain severity was scored on a seven-point Likert scale (0 = no pain; 1 = very little; 2 = slight; 3 = moderate; 4 = relatively severe; 5 = severe; and 6 = as severe as it could be, insufferable pain) and the frequency was shown as pain onset days per week. 13 …”
Section: Methodsmentioning
confidence: 99%
“…The pain severity was scored on a seven-point Likert scale (0 = no pain; 1 = very little; 2 = slight; 3 = moderate; 4 = relatively severe; 5 = severe; and 6 = as severe as it could be, insufferable pain) and the frequency was shown as pain onset days per week. 13 Common mental disorder questionnaires comprising Somatic Self-rating Scale (SSS), Patient Health Questionnaire-15 (PHQ-15), and sevenitem Generalized Anxiety Disorder Scale (GAD-7) were also administered at baseline and week 4. SSS is a highly valid and reliable self-report questionnaire that is primarily used to evaluate emotional responses and somatic symptoms, consisting of 20 items divided into four domains.…”
Section: Questionnairesmentioning
confidence: 99%
“…There is a possibility that using a laxative in bowel cleaning process may induce a significant increase in colonic motility as well as small intestine and colonic volume clearance, thus dissimulating the benefits of probiotics used before colonoscopy. Consequently, it was recommended to utilize probiotics after the colonoscopy procedure, as reported by Li et al, which observed a significant benefit in adding probiotics immediately after the laxative course to IBS patients, rather than using the medications separately [38].…”
Section: Probiotics Utilization Before Colonoscopymentioning
confidence: 99%